Pengaruh Edukasi Pajak, Literasi Digital dan Sistem E-Filling Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Agusetiawati, Wulan Dwi; Askandar, Noor Shodiq; Nandiroh, Umi (e_Jurnal Ilmiah Riset Akuntansi, 2024)
The objectives of this study are as follows: 1) To determine and analyze the effect of tax education, digital literacy and e-filling system simultaneously on individual taxpayer compliance. 2) To determine and analyze the effect of tax education on individual taxpayer compliance. 3) To determine and analyze the effect of digital literacy on individual taxpayer compliance. 4) To determine and analyze the effect of the e-filling system on individual taxpayer compliance. The population in this study were all individual taxpayers registered at KPP Pratama Batu with a sample size of 100 individual taxpayers registered at KPP Pratama Batu. Sample determination using a simple random sampling strategy. The information investigation strategy used to test the theory is multiple linear regression conducted through the Statistical Package for Social Sciences (SPSS) program. The results that emerged were, 1) There is a joint influence between the variables of tax education, digital literacy and the e-filling system on individual taxpayer compliance. 2) Tax education variables affect individual taxpayer compliance. 3) Digital literacy variables affect individual taxpayer compliance. 4) The e-filling system variable affects individual taxpayer compliance.Keywords: Tax education, digital literacy, e-filling system, individual taxpayer compliance.